Flexible MXene‐Based Composite Films: Synthesis, Modification, and Applications as Electrodes of Supercapacitors. Issue 27 (7th June 2022) - Luo, Yijia; Que, Wenxiu; Bin, Xiaoqing; Xia, Chenji; Kong, Bingshan; Gao, Bowen; Kong, Ling Bing
Abstract: MXenes, as a 2D planar structure nanomaterial, were first reported in 2011. Due to their large specific surface area, high ductility, high electrical conductivity, strong hydrophilic surface, and high mechanical flexibility, MXenes have been extensively explored in the development of various functional materials with desired performances. This review is aimed to summarize the current progress in synthesis, modification, and applications of MXene‐based composite films as electrode materials of flexible energy storage devices. In the synthesis of MXenes, the evolution and exploration of etchants are emphasized. Furthermore, in order to develop MXene‐based composite films, the components used to modify the MXene nanoflakes, including 0D, 1D, and 2D nanomaterials, are summarized, and the perspectives and research direction of such materials are also discussed. Abstract : This work focuses on the current progress in the synthesis, modification, and applications of flexible MXene‐based composite films for supercapacitors. The development of the MAX, the evolution of etchants, and the fabrication of MXene films are emphasized. Meanwhile, different components, including 0D, 1D, and 2D and their combinations, are explored to modify MXene nanoflakes, in order to enhance electrochemical performances.